150 The Effect of Day of Surgery and Rehabilitation Utilization on Hospital Length of Stay in Patients Undergoing Elective Meningioma Resection. (August 2015) - Sarkiss, Christopher A.; Lee, James; Papin, Joseph; Yao, Ye; Oermann, Eric Karl; Gordon, Errol; Post, Kalmon D.; Bederson, Joshua B.; Shrivastava, Raj K.
Abstract : INTRODUCTION: Meningiomas account for approximately one-third of brain tumors. Median length of stay (LOS) is 5 days with total charges equaling approximately $55 000. Early rehabilitation improves the functional outcome for patients after surgery. The primary goal was to analyze LOS as a direct result of surgical date and to characterize the individual variables that may impact hospital course, early access to rehabilitation, and long-term functional status. METHODS: A retrospective database was generated of meningioma patients who underwent elective surgical resection at our institution over a 3-year study period (2011-2014). Each record was evaluated for demographics, medical comorbidities, day of surgery, LOS, physical therapy (PT) recommendations, tumor type, insurance status, complications, functional status, and 30-day readmission rates. Given national median LOS of 5 days, we subdivided into 2 cohorts: short LOS (<3 days) and long LOS (≥3 days) for subgroup analysis. Statistical analysis was performed using SPSS 21.0. RESULTS: We identified 140 (25 male, 115 female) patients. Seventy-one had surgery during the early week (Monday-Wednesday) and 69 had surgery in later week (Thursday-Friday). Median age was 58 with median tumor diameter of 3.2 cm. Fifty-six percent of patients had public insurance, and 44% had private with no variation between groups. PT recommendations for rehabilitation were 25% of early patients and 42% of late patients. Medical comorbidities had a strong correlation with respective LOS ( P < .0001, Mann-Whitney test). The median LOS for the early and late populations was 3 and 4 days, respectively. There was a statistically significant short LOS (<3 days) in those patients who underwent surgery early vs those in the later week ( P = .045, Mann-Whitney test). CONCLUSION: Day of surgery plays a significant role in LOS for meningioma patients. Clinicians should remain aware of factors that may delay optimal patient discharge and early access to rehabilitation facilities. Studies are needed to assess the social variables that may affect LOS and the clinical and financial implications for extended hospital courses.